Diagnostic Value of Lipoprotein (a) in Cardiovascular - Yanuartono Yanuartono; Hastari Wuryastuti; R Wasito (Indonesian Association of Food Technologists, 1998)
This research was conducted to evaluate cardiovascular disease caused by atherogenic diets, based on immunological assay by measuring the concentration of lipoprotein (a)/Lp (a). Eighty male Sprague Dawley rats, 150-200 grams' of body weight and three months of age were used in this research. The rats were randomly alloted into four groups, 20 of each. Group I as control was fed normal diet, group 11 was fed diet containing high cholesterol, group 111 was fed diet containing high fat and group 117 was fed diet containing high cholesterol and high fat (atherogenic). After 2, 4, 8, 16 weeks on experimental diet, 20 rats were selected randomly (5 rats of each group), and blood sample were withdrawn for Lp (a) analysis. All animal were then killed and the heart were taken out for histopathological analysis. The statistical analysis for Lp (a), data showed that there were significant differences (p<0.05) among all of the treatments, high fat diet had the greatest influence on Lp (a) concentration. It can be concluded that Lp (aconcentration could be influence by high fat diet, but not by period of treatment. Lp (a) concentration seems connected with the incidence of atherosclerosis in rats. For this reason, evaluation of Lp (a) concentration could be considered as a routine procedure in general health evaluation.